THE ROLE AND PLACE OF THE RIGHTS OF THE LAW IN THE JURISPRUDENCE AND LAW OF IRAN - Soleimani, Abolhassan Mojtahed; Garousi, Naser (International Journal of Psychosocial Rehabilitation, 2020)
the Acquisitive rights are concessions and benefits that each country grants individuals, in order to preserve abusing these rights. It’s a fundamental issue that what is the position of this kind of rights in Iran law and if Iran law recognize this kinds of rights or not? Simultaneously, acquisitive rights are declared in three terms; General, Special, and specific. The foundation of this is also available in the sources of jurisprudence, custom and the judiciary and administrative procedures of Iran. Also the acquisitive rights are significant elements in the way of Guardians council and the court of justice in order to surveillance approaches. Our documentations in this section are containing resolution of Islamic consultative assembly and the votes of Irans general commission. Bases on this research, the acquisitive rights have been recognized by jurisprudence and rights of Iran.